Relationship of Subcutaneous Adipose Tissue Inflammation–Related Gene Expression With Ectopic Lipid Deposition in Persons With HIV. (1st June 2022) - Bailin, Samuel S.; Gabriel, Curtis L.; Fan, Run; Ye, Fei; Nair, Sangeeta; Terry, James G.; Carr, John J.; Silver, Heidi; Wanjalla, Celestine N.; Mashayekhi, Mona; Lima, Morgan; Woodward, Beverly; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objective: Fat redistribution from subcutaneous adipose tissue (SAT) to the abdominal viscera, pericardium, liver, and skeletal muscle contributes to the rising burden of cardiometabolic disease among persons with HIV (PWH). Previous studies found SAT inflammation in PWH impairs lipid storage and persists despite plasma viral suppression on antiretroviral therapy (ART). In this study, we identified SAT immune-related genes associated with ectopic fat deposition in PWH on long-term ART. Design and methods: A total of 92 PWH with well-controlled viremia underwent computed tomography imaging and abdominal SAT biopsy for gene expression analysis. SAT gene expression was measured using a NanoString panel of 255 immune-related genes. Associations between gene expression and computed tomography measurements of the volume and attenuation (radiodensity) of metabolically relevant ectopic fat depots were assessed using multivariable linear regression and network analysis. Results: Greater SAT volume was associated with higher visceral and pericardial adipose tissue volume, but lower skeletal muscle attenuation. Lower SAT attenuation, a measure of lipid content, was associated with lower visceral adipose tissue attenuation. Hierarchical clustering identified a subset of macrophage-related genes in SAT, including CCL2, CCL22, CCL13, CCR1, CD86, CD163, IL-6, IL-10, MRC1, and TREM2, which were associated with an increased lipid deposition in multiple ectopic depots. Conclusion: Altered expression of macrophage-related genes in SAT is associated with differences in ectopic fat depot morphometrics among PWH on long-term ART, including in the pericardial and visceral compartments. These findings provide basis for future studies to assess host, virus, and treatment factors shaping the SAT immune environment and its effects on morphometric changes and metabolic comorbidities in PWH.